2006
DOI: 10.1093/jnci/djj499
|View full text |Cite
|
Sign up to set email alerts
|

Statin Drugs and Risk of Advanced Prostate Cancer

Abstract: In this cohort of male health professionals, use of statin drugs was not associated with risk of prostate cancer overall but was associated with a reduced risk of advanced (especially metastatic or fatal) prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
353
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 370 publications
(376 citation statements)
references
References 28 publications
18
353
3
2
Order By: Relevance
“…Cholesterol-lowering drugs that inhibit the enzyme HMG-CoA reductase, which catalyzes the ratelimiting step in cholesterol synthesis (these drugs are generically termed 'statins'), have been reported to inhibit cancer incidence or progression in some studies. Although there is much controversy, buttressed by claims and counterclaims, in the various population-based reports of the effects of statins on cancer, recent evidence published by several groups examining large prospective series suggest that prostate cancer progression is likely to be inhibited by long-term cholesterol-lowering therapy (Platz et al, 2006;Mondul et al, 2010). These promising results in humans are in agreement with animal model data, in which cholesterol is raised or lowered and prostate tumor growth thereby promoted or inhibited, respectively (Zhuang et al, 2005;Solomon et al, 2009).…”
supporting
confidence: 54%
“…Cholesterol-lowering drugs that inhibit the enzyme HMG-CoA reductase, which catalyzes the ratelimiting step in cholesterol synthesis (these drugs are generically termed 'statins'), have been reported to inhibit cancer incidence or progression in some studies. Although there is much controversy, buttressed by claims and counterclaims, in the various population-based reports of the effects of statins on cancer, recent evidence published by several groups examining large prospective series suggest that prostate cancer progression is likely to be inhibited by long-term cholesterol-lowering therapy (Platz et al, 2006;Mondul et al, 2010). These promising results in humans are in agreement with animal model data, in which cholesterol is raised or lowered and prostate tumor growth thereby promoted or inhibited, respectively (Zhuang et al, 2005;Solomon et al, 2009).…”
supporting
confidence: 54%
“…4,[6][7][8] Supportive evidence for the potential role of cholesterol in prostate cancer development has been provided by observations that cholesterol-lowering drugs (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, commonly known as statins) might be inversely associated with risk of (advanced) prostate cancer. 4,[18][19][20][21] A meta-analysis by Bonovas et al 22 confirmed that use of statins lowers the risk of advanced prostate cancer (relative risk 0.77, 95% CI 0.64-0.93); however, no effect for total prostate cancer risk was found (relative risk 0.95, 95% CI 0.73-1.23). Others proposed that the cholesterol-lowering effects of statins might not be the only reason why these drugs are associated with reduced risk of advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Furthermore, differences in PSA-screening patterns between statin users and non-users might be responsible for the observed associations. 18,22 As results are conflicting and underlying mechanisms have to be elucidated, further research is needed to evaluate the effects of cholesterollowering drugs on prostate cancer prevention, whereas studies on serum cholesterol and other blood lipids should confirm whether these blood lipids itself are potential risk factors for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several clinical studies on statin action in prostate cancer have been reported. Platz et al 43 reported that the use of statins reduced the risk of advanced prostate cancer. Mondul et al 44 observed that the use of statins might protect against prostate cancer with poorer pathological characteristics in prostatectomy patients.…”
Section: Discussionmentioning
confidence: 99%